Monitoring mercury in an urban environment, Umeå, Sweden : Representability and variability of mercury using forest moss biomonitoring in an urban environment - Cañadas Fernandez, Manuel (Umeå universitet, Institutionen för ekologi, miljö och geovetenskap, 2017)
The objective of my project was to determine variability and representability of mercury in the urban environment of Umeå in northern Sweden, based on applying the methods of forest moss biomonitoring (Swedish Environmental Protection Agency, ICP Manual). Mercury (Hg) is a commune pollutant in urban environments release to the atmosphere by anthropogenic activities. Industrial, traffic and incineration activities are the main sources of this element. Mercury is easily transported through the atmosphere and cycle through terrestrial and aquatic ecosystems, trending to bioaccumulate in organisms. The aims of the study are: (1) determine the representability and variability of the method in a specific urban environment, based on more intensive analyses of a green area within the city boundaries of Umeå, northern Sweden. (2) influence of site-specific conditions on the concentration of mercury in mosses. (3) City-scale variability in relation to national forest moss biomonitoring data (IVL.se). Results of urban environment measurements do not differ much respect the values of mercury concentration obtained sampling mosses far from the city, but it is subject to many factors that can alter results of the study.Â Most of these are meteorological factors and the difficulty of find green zones close to cities with the suitable conditions to find mosses and perform a property sampling process avoiding throughfall and litterfall. The conclusion is that the use of mosses is a representative and valuable method to obtaining information in an urban environment but is limited by mentioned factors.